The Effect Of Company Financial Performance On Bond Ratings With GCG As Moderating Variable - Ronny Firmansyah Nirwana; Bambang Subroto; Aulia Fuad Rahman (University of Merdeka Malang, 2022)
This study aims to test and empirically prove the effect of the independent variables (return on assets, current ratio, debt to equity ratio and total asset turnover) on the dependent variable, namely bond ratings, with Good Corporate Governance (GCG) as moderating variable (independent commissioners, institutional ownership, managerial ownership and audit committee). The research data uses non-financial companies sourced from www.idx.co.id and the official website of PT PEFINDO in the 2015-2020 period with a total sample of 261 companies. The results of the study found that return on assets, current ratio and debt to equity ratio had an effect on bond ratings, while total asset turnover had no effect on bond ratings. GCG does not significantly strengthen or weaken the relationship of return on assets, current ratio, debt to equity ratio and total asset turnover to bond ratings.